Grades and Employer Learning - Anne Toft Hansen; Ulrik Hvidman; Hans Henrik Sievertsen (Institute of Labor Economics (IZA), 2021)
This study examines the labor-market returns of skill signals. We identify the labor-market effect of grade point averages (GPA) by leveraging a nationwide change in the scaling of grades in Danish universities. Results show that a reform-induced increase in GPA that is unrelated to ability causes higher earnings immediately after graduation, but the effect fades in subsequent years. The effect at labor-market entry is largest for individuals with fewer alternative signals and the earnings adjustment occurs both within and across firms. Although employers initially screen candidates based on skill signals, our findings suggest that they rapidly learn about worker productivity.
Keywords: I20; J20; I26; 330; employer learning; job-market signaling; higher education